Fractal surface analysis and thermodynamic properties of moisture sorption of calcium–sucrose powders. Issue 9 (4th July 2018) - Flores-Andrade, E.; Pascual-Pineda, L. A.; Quintanilla-Carvajal, M. X.; Gutiérrez-López, G. F.; Beristain, C. I.; Azuara, E.
ABSTRACT: Fractal analysis, using water adsorption and an image analysis technique, was applied to investigate the effect of surface irregularities on the thermodynamic properties of matrix calcium–sucrose powder moisture sorption. The sorption isotherms were evaluated at 15, 25, and 35°C for calcium–sucrose powders obtained by a cryogenic process (CP) and spray drying (SD). Solubilization of the powders was observed after 20 days of storage at 25°C, and the powder CP had greater physical stability than SD. There was good agreement among the fractal dimension computed by scanning electron microscopy analysis and water adsorption isotherm. The surface fractal dimensions were between 2.19 and 2.44 for CP and were larger than those obtained for SD, which were between 2.11 to 2.26. The differential and integral enthalpies increased as the surface geometry became more irregular, also increased the interactions between the powder surface and water molecules. These results suggested that the increase in the matrix irregularities for a product can displace the minimum integral entropy toward high water activity, thereby improving the storage stability.